2017
DOI: 10.1016/j.bbmt.2017.05.032
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Based Therapy Using Umbilical Cord Blood for Novel Indications in Regenerative Therapy and Immune Modulation: An Updated Systematic Scoping Review of the Literature

Abstract: Cell-based therapy using umbilical cord blood (UCB) is being used increasingly in novel applications. To balance heightened public expectations and ensure appropriateness of emerging cell-based treatment choices, regular evidence-based assessment of novel UCB-derived therapies is needed. We performed a systematic search of the literature and identified 57 studies (814 patients) for analysis. Sixteen of these studies (353 patients) included a control group for comparison. The most commonly reported novel indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
39
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 51 publications
0
39
0
1
Order By: Relevance
“…Researchers are also optimizing manufacturing procedures to improve CB product quality 5 and many studies are exploring novel therapeutic applications for CB. 6 Essential to a successful research program is a reliable, quality-controlled and ethically sourced supply of CB. A 2009 survey of investigators estimated that 2000 CB units per year were needed to support Canadian researchers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers are also optimizing manufacturing procedures to improve CB product quality 5 and many studies are exploring novel therapeutic applications for CB. 6 Essential to a successful research program is a reliable, quality-controlled and ethically sourced supply of CB. A 2009 survey of investigators estimated that 2000 CB units per year were needed to support Canadian researchers.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the low number of SCs in a CB unit has limited this treatment to the realm of pediatric medicine, although double‐CB transplantations are being performed in larger children and adults and SC expansion protocols are being tested in the clinic (reviewed in 2015 by Pineault and Abu‐Khader). Researchers are also optimizing manufacturing procedures to improve CB product quality and many studies are exploring novel therapeutic applications for CB . Essential to a successful research program is a reliable, quality‐controlled and ethically sourced supply of CB.…”
mentioning
confidence: 99%
“…Several sources have been thus reported such bone marrow (BM) , adipose tissue (AT) (Busser et al 2015), foreskin (Najar et al 2016a) and dental pulp (Kang et al 2016) with contrasting results. Embryonic tissues like placenta (Lee et al 2012) and umbilical cord (CB) (Rizk et al 2017) seem to be important alternatives. The gelatin that surrounds the umbilical cord vessels called Wharton's jelly (WJ) is very promising; indeed, the WJ-MSCs have been discovered to be an ideal source of stromal cells (Beeravolu et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Translational and clinical research in cell‐based regenerative medicine has demonstrated significant promise with an increasing number of clinical and preclinical studies involving the use of blood, marrow, umbilical cord blood, and various cell types including mesenchymal stem cells and endothelial progenitors . There is significant and growing interest for the potential of this new field of medicine.…”
mentioning
confidence: 99%
“…T ranslational and clinical research in cell-based regenerative medicine has demonstrated significant promise with an increasing number of clinical and preclinical studies involving the use of blood, marrow, umbilical cord blood, and various cell types including mesenchymal stem cells and endothelial progenitors. [1][2][3][4] There is significant and growing interest for the potential of this new field of medicine. As more studies are performed and more patients are enrolled in clinical trials that will inform and shape clinical practice, researchers and clinicians will rely increasingly on the ability to access and use clinical-grade cells donated from healthy donors as starting material for the development of emerging cellbased therapies.…”
mentioning
confidence: 99%